Penguatan Branding Produk dan Digital Marketing di Era Cyber Physical System - Kurniawan, Fajar Adhi; Hakim, Muh. Luthfi; Mahmudi, Ali (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2023)
The development of Information Technology in the era of industrial revolution 4.0 or cyber physical system requires business actors to adapt and develop appropriate responses, including through product branding and digital marketing. This service aims to improve product branding and digital marketing for small and medium enterprises (SME) in Jepara Regency. The approach used is the Asset Based Community Development (ABCD), this approach is considered relevant for exploring existing SME assets. The results of this service show; First, SME actors are committed to and implement the results of the training by utilizing updated promotional content, logos and sales pages. Second, the implementation of the entire training program that has been scheduled which targets business product development through product branding and digital marketing strategies has succeeded in improving product owners from branding and digital marketing aspects as a response to SME in the cyber physical system era. On an ongoing basis, this program can be used to expand target markets and increase sales and the economy of SME in Jepara Regency.